HC-05 PROTOCOL IOT BASED FOR SMART WEARABLE HEART-RATE MONITORING SYSTEM WITH BLYNK APPLICATION - Azwati Azmin; Aiza Mahyuni; Zafirah Faiza; Najwa Rawaida Ahmad; Rabiatul Adawiyah Akhbar; Wan Mohd Yusof Rahiman (Journal of Islamic, Social, Economics and Development, 2022)
Incorporating technology in emergency healthcare would tremendously help to further enhance the quality of patient’s care. The application of Internet of Things or IoT into emergency healthcare could be the better digital solutions to saving lives in the time of rush. The patient’s vital signs, TRIAGE tags and conditions could be updated to the doctors in the emergency department without lag. Both parties can also communicate with one another to discuss the patient’s treatment. This welcomes more possibilities in telemedicine and disaster management. Patients who suffered from serious illness issues such as heart attack, other respiratory failures and sudden rise in body temperature need at least IoT based wearable health monitoring systems for continuous physiological data monitoring in real-time basis. This wearable health monitoring systems can provide better transformation information compare to the general health issues for each individuals. The implementation of IoT based wireless technologies in this project create a new alternative way in the medical stuff to convert the conventional health care system, by replacing the current practice to a wearable monitoring vital sign systems, which is more efficient. The objective for this research is to develop a wearable device capable of monitoring and transmitting vital signal patients in real-time basis and to create low-cost, greater mobility for a doctor to provide consultation to the patient in prompt action. In specific, wireless devices and techniques for monitoring heart, pulse rate and temperature are discussed.